2018
DOI: 10.1002/mrm.27493
|View full text |Cite
|
Sign up to set email alerts
|

isoPhasor: a generic and precise marker visualization, localization, and quantification method based on phase saddles in 3D MR imaging

Abstract: Purpose To derive a generic approach for accurate localization and characterization of susceptibility markers in MRI, compatible with many common types of pulse sequences, sampling trajectories, and acceleration methods. Theory and Methods A susceptibility marker’s dipolar phase evolution creates 3 saddles in the phase gradient of the spatial encoding, for each sampled data point in k‐space. The signal originating from these saddles can be focused at the location of the marker to create positive contrast. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Previous works in MR-based fiducial marker detection are mainly based on template matching using either signal voids on magnitude images or field distortions on phase images; although the aforementioned methods have been effective under certain conditions (orientation, dimensions, shape), clear marker depiction with positive contrast similar to CT was not achieved (Bouwman, Custers, Bakker, Viergever, & Seevinck, 2019;Ghose et al, 2016;Jonsson, Garpebring, Karlsson, & Nyholm, 2012). Our results with QSM showed that the relative location of the markers was identical with the CT image indicating the possibility of using QSM in MR-guided EBRT for the disease sites like prostate, liver and lung.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works in MR-based fiducial marker detection are mainly based on template matching using either signal voids on magnitude images or field distortions on phase images; although the aforementioned methods have been effective under certain conditions (orientation, dimensions, shape), clear marker depiction with positive contrast similar to CT was not achieved (Bouwman, Custers, Bakker, Viergever, & Seevinck, 2019;Ghose et al, 2016;Jonsson, Garpebring, Karlsson, & Nyholm, 2012). Our results with QSM showed that the relative location of the markers was identical with the CT image indicating the possibility of using QSM in MR-guided EBRT for the disease sites like prostate, liver and lung.…”
Section: Discussionmentioning
confidence: 99%